2021
DOI: 10.3390/v13122372
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Human Herpes Viruses to γδ T Cell Mobilisation in Co-Infections

Abstract: γδ T cells are activated in viral, bacterial and parasitic infections. Among viruses that promote γδ T cell mobilisation in humans, herpes viruses (HHVs) occupy a particular place since they infect the majority of the human population and persist indefinitely in the organism in a latent state. Thus, other infections should, in most instances, be considered co-infections, and the reactivation of HHV is a serious confounding factor in attributing γδ T cell alterations to a particular pathogen in human diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 309 publications
0
5
0
Order By: Relevance
“… 23 Some studies have demonstrated that a high incidence of herpesvirus reactivation is associated with patients admitted to the intensive care unit for severe COVID‐19. 24 , 25 Thus, according to de evidence, it is not preposterous to hypothesize that the SARS‐CoV‐2 virus might be a biological trigger agent for this autoimmune condition. 21 However, long‐term studies will shed light on this hypothesis to determine the possible etiopathogenic role of SARS‐CoV‐2 as a trigger agent for achalasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 Some studies have demonstrated that a high incidence of herpesvirus reactivation is associated with patients admitted to the intensive care unit for severe COVID‐19. 24 , 25 Thus, according to de evidence, it is not preposterous to hypothesize that the SARS‐CoV‐2 virus might be a biological trigger agent for this autoimmune condition. 21 However, long‐term studies will shed light on this hypothesis to determine the possible etiopathogenic role of SARS‐CoV‐2 as a trigger agent for achalasia.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Facco et al have identified an oligoclonal lymphocytic infiltrate within the LES of achalasia patients with the ability to recognize human HSV‐1 antigens associated with increased proliferation and Th1‐type cytokines release 23 . Some studies have demonstrated that a high incidence of herpesvirus reactivation is associated with patients admitted to the intensive care unit for severe COVID‐19 24,25 . Thus, according to de evidence, it is not preposterous to hypothesize that the SARS‐CoV‐2 virus might be a biological trigger agent for this autoimmune condition 21 .…”
Section: Discussionmentioning
confidence: 99%
“…24 Some studies have demonstrated that a high incidence of herpesvirus reactivation is associated in patients admitted to the intensive care unit for severe COVID-19. 25,26 Thus, according to de evidence, it is not preposterous to hypothesize that the SARS-CoV-2 virus might be a biological trigger agent for this autoimmune condition. 22 However, long-term studies will shed light on this hypothesis to determine the possible etiopathogenic role of SARS-CoV-2 as a trigger agent for achalasia.…”
Section: Discussionmentioning
confidence: 99%
“…42 Children with uncomplicated malaria showed an increased expression of CD16 + on Vδ1 + T cells, although there was a possibility of co-infection with cytomegalovirus, which is known to induce CD16 + -expressing Vδ1 + T cells. 43 Therefore, further studies are needed to investigate role of coexisting infection in Vδ1 + T-cell response.…”
Section: Response Of Human γδ T Cells To Plasmodium Parasitesmentioning
confidence: 99%